2009
DOI: 10.1137/080717043
|View full text |Cite
|
Sign up to set email alerts
|

Time-Minimal Control of Dissipative Two-Level Quantum Systems: The Integrable Case

Abstract: The objective of this article is to apply recent developments in geometric optimal control to analyze the time minimum control problem of dissipative two-level quantum systems whose dynamics is governed by the Lindblad equation. We focus our analysis on the case where the extremal Hamiltonian is integrable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…We then search for the time-minimum control field, which drives the system from S to M . The general solution of the time-optimal control problem has been given in a series of papers, both for the bounded [5,19,20] and the unbounded cases [21]. It can be shown that the structure of the time-optimal control law can be mainly described by two geometric objects of the Bloch ball which play a central role in the present analysis: the magic plane of equation…”
Section: The Model Systemmentioning
confidence: 99%
“…We then search for the time-minimum control field, which drives the system from S to M . The general solution of the time-optimal control problem has been given in a series of papers, both for the bounded [5,19,20] and the unbounded cases [21]. It can be shown that the structure of the time-optimal control law can be mainly described by two geometric objects of the Bloch ball which play a central role in the present analysis: the magic plane of equation…”
Section: The Model Systemmentioning
confidence: 99%
“…In this case the purity ρ of the system cannot be controlled and the study of the extremals reduces to the analysis of the geodesics of the Grushin metric on the two sphere of revolution, which was done in [6]. The geodesics are a) meridian circles or b) periodic trajectories in the plane (φ, p φ ) withθ periodic.…”
Section: Classification Of the Asymptotics Of The Extremal Solutionsmentioning
confidence: 99%
“…There are several reasons to consider that for the time-minimal control problem, the smooth continuation method is well adapted to analyze the system. Indeed, from our previous study [6,12] we know that when Γ = γ + and γ − = 0, the time-minimizing control problem can be reduced to analyze the quasi-Riemannian metric…”
Section: Introductionmentioning
confidence: 99%
“…The control problem consists of finding a trajectory of the state variables solving (5), starting at the completely mixed state (i.e., r = 0) and ending at the apogee. It is important to note, however, that the dynamics (5) has a singularity at the origin since…”
Section: Introductionmentioning
confidence: 99%